The right to the truth of victims of a repressive regime in the international public law - Stevanović Miroslav (Temida, 2016)
The break-up with the repressive regime, and above all rehabilitation of the consequences for victims, includes determining the truth about the character, carriers and methods of systematic violation of basic human rights. Many international instruments, which deal with the problem of victims of repressive regimes and the state discontinuity with repressive governance, proclaim the concept of the right to the truth. The paper deals with the normative contents of the right to the truth and different aspects of this concept that international courts recognize in relation to victims of repressive regimes. The results of the analysis indicate that the concept of the right to the truth sets before the states requirements to try to provide institutional preconditions for individual and collective victims to find out and access the truth, but that the case-law does not recognize as enforceable any authorisation which stems from the right to the truth. Currently, the right to the truth presents a principle that relates to realising some internationally protected rights of a person, but there are indications that it has been normatively shaping in order to become a legal principle of transition.